Analysis of Students' Understanding in Using Rhetorical Moves on Thesis Abstract - Agung Suhadi (Institut Agama Islam Negeri Palopo, 2022)
This paper presents the study of rhetorical moves on thesis abstracts of accounting students at the Muhammadiyah University of Bengkulu. The motive of this research is to examine how far students' understanding is in using rhetorical moves in their thesis abstracts. Under the qualitative descriptive method, 20 abstracts are taken randomly based on the thesis abstract, which was being proofread at Language Center Muhammadiyah University of Bengkulu, 2021. Data were further discussed in the light of rhetorical moves by Swales. Based on the results of the analysis, this study revealed different forms of rhetorical moves; the highest sequence and frequency on Move 3 (research method) and Move 4 (results) were 100% occurrences according to Jhon Swales' concept. Furthermore, move 2 (research aim) has a higher sequence and frequency, it was 80% occurrence. Unsimilar, move 1 (situating research) and Move 5 (conclusion) as the smallest sequence and are frequent due to the abstracts not correctly presenting some steps of rhetorical moves as proposed by Swales. To sum up, this study has set out the findings; mostly accounting students have followed the rhetorical moves in their thesis abstracts on Move 3 and Move 4. However, their understanding of Move 1 and 5 must be revised for generating better abstracts.